2004
DOI: 10.1111/j.1365-2222.2004.01952.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with intranasal fluticasone propionate significantly improves ocular symptoms in patients with seasonal allergic rhinitis

Abstract: Patients treated with intranasal FP had clinically and statistically significant decreases in ocular symptom scores compared with vehicle placebo. Data also suggest that FP reduced ocular symptoms more than or comparable with oral LOR. Patients experiencing ocular symptoms associated with allergic rhinitis may benefit from monotherapy with intranasal FP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 26 publications
3
56
0
1
Order By: Relevance
“…[15,16] Intranasal corticosteroids are often required in moderate to severe disease and are effective in reducing all symptoms of allergic rhinitis in addition to eye symptoms associated with allergic conjunctivitis. [17,18] Leukotriene levels are increased in the early as well as the late phase of the allergic reaction. Nasal insufflation studies show that both leukotriene C4 (LTC4) and leukotriene D4 (LTD4) induce an increase in nasal mucosal blood flow and nasal airway resistance.…”
Section: Discussionmentioning
confidence: 99%
“…[15,16] Intranasal corticosteroids are often required in moderate to severe disease and are effective in reducing all symptoms of allergic rhinitis in addition to eye symptoms associated with allergic conjunctivitis. [17,18] Leukotriene levels are increased in the early as well as the late phase of the allergic reaction. Nasal insufflation studies show that both leukotriene C4 (LTC4) and leukotriene D4 (LTD4) induce an increase in nasal mucosal blood flow and nasal airway resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The rationale for using intranasal glucocorticosteroids in the treatment of allergic rhinitis is that high drug concentrations can be achieved at receptor sites in the nasal mucosa with a minimal risk of systemic adverse effects. These medications are effective in improving all symptoms of allergic rhinitis as well as ocular symptoms (1559)(1560)(1561). If nasal congestion is present or symptoms are frequent, an intranasal glucocorticosteroid is the most appropriate first-line treatment as it is more effective than any other treatment (1562,1563).…”
Section: Intranasal Glucocorticosteroidsmentioning
confidence: 99%
“…Bernstein et al performed a double-blind, doubledummy, randomized study comparing fluticasone propionate aqueous nasal spray 200 mg once daily, oral loratadine 10 mg once daily or placebo for the treatment of seasonal allergic rhinitis and found that fluticasone propionate reduced ocular symptoms, especially ocular itching, tearing and redness, compared with not only placebo but also oral loratadine [85]. More recently, Fokkens et al performed a multi-centre, randomized, double-blind, placebocontrolled, parallel group study of fluticasone furoate 110 mg once daily nasal spray versus placebo for the treatment of seasonal allergic rhinitis caused by grass pollen, and they found that fluticasone furoate is significantly effective for not only nasal symptoms and quality of life but also ocular symptoms including eye itching/burning, eye tearing/ watering and eye redness [86].…”
Section: Effect Of Ins On Ocular Symptoms In Patients With Allergic Rmentioning
confidence: 99%